(untitled) (Physical Education, Health and Social Sciences, 2025)
Memories are always a special part of our lives, and with every moment we make memories that become the record in our conscious and subconscious minds, but the record of memories as photographs is a precious treasure, and it is a universal language. Today, after all these years of industrialization, it’s not just about changing perceptions in taking photographs and recording a moment; it’s also about changing the way we experience it, from colourless photography to colorful, from shades to backgrounds, from an old camera to new digital media, from a few clicks of precious moments (Polaroid photographs) to uploading on social media. This abstract will reflect the idea of inventing the photograph and the value of recording memory and history that influence personal and social identities. It is worth considering what the camera has captured and what has happened afterwards.What is this new vision of life and human being that emphasizes the importance of image as a record? What is the need for creating a family photographic tradition? How have artists viewed archives as art?